Ultraviolet Radiation-Induced Skin Aging: The Role of DNA Damage and Oxidative Stress in Epidermal Stem Cell Damage Mediated Skin Aging. (11th April 2016) - Panich, Uraiwan; Sittithumcharee, Gunya; Rathviboon, Natwarath; Jirawatnotai, Siwanon
Abstract : Skin is the largest human organ. Skin continually reconstructs itself to ensure its viability, integrity, and ability to provide protection for the body. Some areas of skin are continuously exposed to a variety of environmental stressors that can inflict direct and indirect damage to skin cell DNA. Skin homeostasis is maintained by mesenchymal stem cells in inner layer dermis and epidermal stem cells (ESCs) in the outer layer epidermis. Reduction of skin stem cell number and function has been linked to impaired skin homeostasis (e.g., skin premature aging and skin cancers). Skin stem cells, with self-renewal capability and multipotency, are frequently affected by environment. Ultraviolet radiation (UVR), a major cause of stem cell DNA damage, can contribute to depletion of stem cells (ESCs and mesenchymal stem cells) and damage of stem cell niche, eventually leading to photoinduced skin aging. In this review, we discuss the role of UV-induced DNA damage and oxidative stress in the skin stem cell aging in order to gain insights into the pathogenesis and develop a way to reduce photoaging of skin cells.